Microplate-reader method for the rapid analysis of copper in natural waters with chemiluminescence detection - Durand, Axel; Chase, Zanna; Remenyi, Tomas; Queroue, Fabien (Frontiers in Microbiology, 2013)
We have developed a method for the determination of copper in natural waters at nanomolar levels. The use of a microplate-reader minimises sample processing time (~ 25 sec per sample), reagent consumption (~ 120 μL per sample) and sample volume (~ 700 μL). Copper is detected by chemiluminescence. This technique is based on the formation of a complex between copper and 1,10-phenanthroline and the subsequent emission of light during the oxidation of the complex by hydrogen peroxide. Samples are acidified to pH 1.7 and then introduced directly into a 24-well plate. Reagents are added during data acquisition via two reagent injectors. When trace metal clean protocols are employed, the reproducibility is generally less then 7% on blanks and the detection limit is 0.7 nM for seawater and 0.4 nM for freshwater. More than 100 samples per hour can be analyzed with this technique, which is simple, robust, and amenable to at-sea analysis. Seawater samples from Storm Bay in Tasmania illustrate the utility of the method for environmental science. Indeed other trace metals for which optical detection methods exist (e.g. chemiluminescence, fluorescence and absorbance) could be adapted to the microplate-reader.